2020 Quota Data Update. (Policy Papers; Policy Paper, 2021)
This paper presents the annual update of the quota database and extends the database by one year through 2018. The paper provides an overview of the data and of the methodology and covers the quota formula variables and calculated quota shares based on the current quota formula.